EVALUATION OF GENETIC DIFFERENCES ON IMMUNOLOGICAL RESPONSE IN TWO NATIVE CHICKEN STRAINS FED ON DIFFERENT NATURAL AND ORGANIC ACID SUPPLEMENTATION - Eman S. Osman; E.A. Abdallah; A.G. Elsayed; A.H. Elattar (Arab Universities Journal of Agricultural Sciences, 2018)
The main objective of this study was to investigate the effect of the genetic differences in immunological response by use the natural growth promoters in diets offered to local chicken strains (GoldenMontazah (GM) and Bandra (B)). The present study was carried out in Seds Poultry Breeding Research Station, Animal Production Research Institute, Banysweif Governorate, through August to January (2016). A total of 240 chicks (120 hens of each strain) were used from 16 to 40 weeks of age. Birds were randomly distributed into six treatments. Each treatment had 20 (female) chicks (20X 6X 2) that were individually caged. The first treatment of each strain served as a control group and fed the formulated basal diet without any tested feed additives. The second treatment fed the basal diet with BioPlus® 2B, (400gm/ton) a commercial probiotic preparation (pro. (Bio)). The third treatment hens were fed the same basal diet with the addition of TechnoMos® (500gm/ton) a prebiotic type (pre. (Tech)).The fourth treatment fed the basal diet with Diamond V®(2.5kg/ton) a commercial prebiotic produced (pre. (Dia)). The fifth treatment fed the basal diet with FORMI® NDF (2kg/ton) (organic acid (FORMI)). The sixth treatment fed the basal diet with combination of (BioPlus® 2B, (400gm/ton) + TechnoMos® (500gm/ton) + FORMI® NDF (1kg/ton)) (combination (BTF)).  Data showed that, the Heterophils/Lymphocyte ratio percentage value was significantly higher in  Golden Montaza than Bandara. The highest value was found for organic acids (FORMI) group and the lowest value was found for probiotic (Bio Plus) group.  As for the antibody titer before vaccination the highest values were found for pre (Tech) group in comparison to pre (Dia) group. And there were no significant differences between the control group and all treated groups. Also, the higher values of antibody titer against Newcastle vaccine after vaccination were found in pre (Tech.), org ((FORMI), combination (Bio, Tech and FORMI) and control groups compare to values were found in pre (Dia) and pro (Bio) groups. As for the differences titer between before and after vaccination against Newcastle disease virus, there were no significant differences.